Pengaruh Ukuran Dewan Direksi Terhadap Profitabilitas Perusahaan BUMN Di Indonesia Dengan Kepemilikan Pemerintah Sebagai Variabel Moderating - Suci Nurulita (Jurnal Akuntansi Keuangan dan Bisnis, 2015)
The main purpose of the establishment of Board Size is to maximize the value of the company with the implementation of independent and professional management based on high moral values and compliance with the legislation in force. To achieve profitability the company can not be separated from the participation of all the Board of Directors to develop the company towards progress. The population of this study was all of the 25 State-Owned Enterprises (SOEs) registered in the Indonesian Stock Exchange from 2003-2014 and 12 of them were selected to be the samples for this study through purposive sampling method. The data obtained were multiple linear regression method with SPSS version 22. The results of this study showed that partially the variable of Board Size and Government Ownership had a negative significant influence on profitability of the company. Government ownership moderated the relationship between Board Size and the  profitability of the SOEs in Indonesia.Keywords: Board Size, government ownership, profitability.